The Old Sea of Guayaquil. Guayas River Basin. - Marín-Nieto, Luis (Revista Universidad de Guayaquil, 2011)
A great channel of 1.3 km depth from the Tertiary, separating the Andes in the Cordillera Chongón Colonche was constantly filled mudslides, volcanic products and possible lava flows, particularly in Santo Domingo, Quevedo and Cochancay, where they formed large alluvial fans in the current header Daule, Peripa and Baba, north, center and Catarama San Pablo, and South, rivers Chimbo Bulubulu and Cañar. This paper attempts to summarize the outcome in the XX and XXI Century several investigations in post Wolf Guayas Basin of Geotechnical and Hidrogeotécnicas character, based on the main field andlaboratory work it, and in which the author has participated since 1964, both in the river Basin Daule, Peripa and Babahoyo, dominated the Guayas river as in the Lower Basin. The purpose of this paper is to provide a useful tool on the horizon that are facing climate change, increased urban, the threat of desertification, land use planning and the ecological flow, that requirea practical background on the origin of the Guayas River Basin.
Keywords: Hidrogeotecnia; Basin; floodplains; drainage patterns alluvia; volcanic-Marines Soil; Erosion; alluvial soil; El Niño; ecological flows